A requirements management tool for small and medium projects: An industrial case study - Zainol, Azida (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2013)
In the previous years, there are many requirements management tools available in the market.However, these tools are expensive, complicated, difficult to learn and too sophisticated for small and medium projects. This paper presents a case study of implementing a Requirements Management Tool for small and medium projects (RMT-SMP) in the real industry in order for the RMT-SMP to be feasible for small and medium projects. The case study carried out by defining the hypothesis, selection of the pilot study, identification of different methods of comparison, consideration of the effects of cofounding factors, planning of the case study, monitoring the case study as well as result analysis and report generation.The results have shown that the RMT-SMP is practical and feasible for the small and medium projects in the Malaysian software industry and encourages the practitioners to have a better approach in managing their requirements during software development projects.